THE GILCHRIST SCHOLARSHIP AND THE UNIVERSITY OF LONDON IN THE EARLY DEVELOPMENT OF HIGHER EDUCA· TION FOR THE CAPE COLONY (Historia, 2021)
In November, 1872 the Superintendent General of Education for the Cape Colony, Langham Dale, received" ... the gratifying intelligence of Mr. Kolbe's success..." in the matriculation examination of the Univer·sity of London held in Cape Town the previous June. 1 Placed sixth in the honours division, Frederick Charles Kolbe, son of a German Protestant missionary, student at the South African College and future distinguished convert to the Catholic Church, was awarded the Gilchrist Scholarship for graduate study in the United Kingdom
Keywords: Gilchrist Scholarship; Gilchrist, J.B; Higher education; John Borthwick; Gilchrist; Cape Colony; University of London